Perceptions of students on their tutors in an innovative medical curriculum - Bornales, Dante P.
Objectives: The general objective of this study was to determine the perceptions of the medical students in Manila Central University -Filemon D. Tanchoco Medical Foundation College of Medicine (MCU-FDTMF CM) toward their tutors during the small group tutorial sessions of the Innovative Medical Curriculum. The specific objectives are: (1) to determine the perceptions of the students on the facilitating behavior of their tutors; (2) to describe the varying perceptions of the students according to whether the tutors were content experts or not; and (3) to identify the factors that significantly correlated with the students' perceptions on their tutors. This is a descriptive study involving 117 second and third year medical students enrolled during the second semester of academic year 2004-2005 and 14 SGL tutors of MCU-FDTMF CM. A Likert-type opinionaire adapted from Dolmans and Ginns (2004) PBL faculty evaluation scale was used with author's permission. The instrument was anchored on the constructivists' contemporary learning strategies based on: constructive/active learning, self-directed learning, contextual learning, and collaborative learning. The responses of the students were compared with the tutor characteristics and analyzed using Kruskal-Wallis and Mann-Whitney u test. Spearman coefficient of correlation was used to correlate other tutor variables. Results: There were 44 second year and 73 third year medical students who were surveyed. The overall median responses of the students toward their perceptions on their tutors' behavior during the small group tutorial sessions were favorable. Content expert tutors were perceived by the students as more effectively stimulating them on the self-directed and collaborative learning strategies. The other parameters of the constructivists' learning strategies have no statistical significance comparing the content expert and the non-content expert tutors. The tutors with lesser number of years as faculty of the college and as SGL tutor were perceived to be more effectively stimulating the students on certain items in the self-directed learning, contextual learning, and collaborative learning strategies. Conclusions: There are certain tutor characteristics that the students perceive as factors that stimulate them to function effectively in the SGL. Content expert tutors were favorably perceived by the students as effectively stimulating them toward self-directed learning and collaborative learning during the SGL.